PENGARUH KEAMANAN, KEPERCAYAAN, DAN PERSEPSI RISIKO TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE PADA LAZADA ONLINE SHOP (Studi Pada Mahasiswa Fakultas Ekonomi Universitas Negeri Medan) - Hidayat, Toni; Teviana, T (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Medan, 2016)
This research aims to identify and explain the effect of security, trust, and perceived risk in online purchase decisions at the college student of the Faculty of Economics, State University of Medan. either partially or simultaneously.This research conducted at Faculty of Economics, State University of Medan. Sample size of this research is 96 respondents. College student who become respondents came from the Departments of Management, Department of Economics, and Department of Accounting. Data collection technique used was through a questionnaire which was measure using Likert scale and statistically analyzed using multiple regression analysis withÂ structural education Y=a+b1X1+b2X2+b3X3+e and processed with SPSS for windows 23.00.The result showed that the security (X1), trust (X2), and perceived risk (X3) simultaneously significantly influence the purchase decision (Y). This is evident from the calculated Fvalue of 18.723 and Ftable of 2,70, so the Fvalue of 18.723 > Ftable of 2,70 of the significance Î± = 5%. Where the influence of the variable security, trust, and perceived risk in the purchase decisions is 37,9% as indicated by the value of R square is 0.379. while the partial security has a influence on purchasing decisions with the tvalue> ttable is 2,655 > 1,985, trust has a influence on purchasing decisions with the tvalue> ttable is 3,331 > 1,985, but perceived risk has not a influence on purchasing decisions with the tvalue<Â ttable is -1.096 < 1,985. Structural equation of the model at can be made with Y=1,595+0,252X1+0,359X2-0,095X3+e.Â Key Word: Security, Trust, Perceived Risk And Online Purchase Decisions